Critical analysis for evaluating maximum power point tracking strategy in photovoltaics and fuel cells using key performance metrics - Zuhair Alyousef; Oscar D. Crisalle (Energy Reports, 2023)
This study performs detailed analyses to investigate and justify the utilization of maximum power point tracking (MPPT) algorithm in photovoltaics (PV) and fuel cells. Two devices are parallelly analyzed to establish a comparative and contrasting study on the performance of the two technologies at MPP regime for a given operational condition. Direct methanol fuel cell (DMFC) is chosen as a representative of the hydrogen fuel cells family. The operational variables affecting the electrical power in the devices, including temperature (for both devices), solar irradiance (for PV cells), and methanol concentration (for DMFC) are discussed, along with their similarities and differences. Voltage losses are addressed to gain insights into the electrical quality of each device at MPP regimes. Due to their pivotal role, fuel availability and cost, energy losses, overall efficiency, and cathode flooding are selected as crucial performance metrics to compare the two technologies at MPP. The results demonstrate that PV cells have a good voltage quality at MPP with an average retention of 87% from open-circuit voltage VOC, whereas DMFC performance deteriorates at MPP, resulting in a significant decline with a loss of 61% from VOC . Consistent with voltage loss results, fill factor analysis at MPP zones lead to the same conclusion wherein photovoltaics offer high fill factor of approximately 82%, whereas DMFC has lesser values that are below 40%. The maximum overall efficiency of PV cells is attained at the MPP zones, whereas optimal efficiencies do not match the MPP loci in fuel cells. Simulations show that DMFC is extremely prone to cathode flooding at MPP zones, where approximately 90% of pore spaces in the liquid distribution layer are occupied with water. Conversely, PV cells are completely free from such issues. Some recommendations for further advancement and investigation on the use of MPPT in both technologies are provided.